Vihreän siirtymän ja digitalisaation tuet Suomessa - Otto Kässi (The Research Institute of the Finnish Economy (ETLA), 2024)
– This report examines the allocation of Finland's green transition and digitalization-related subsidies on an an- nual basis. The analysis utilizes the business subsidy in- formation service system maintained by the Ministry of Economic Affairs and Employment, which provides com- prehensive data for the years 2020-2023. According to the data, the value of green subsidies has increased both relatively and absolutely since 2020. However, on an an- nual basis, the share of brown subsidies, which increase greenhouse gas emissions, has been larger than that of green subsidies every year. There is no similar growth trend for subsidies aimed at digitalization. Moreover, the value of subsidies directed towards digitalization is low- er than brown subsidies on an annual level. A provincial and sectoral comparison of the subsidies reveals that a significant portion of the subsidies is narrowly targeted to specific sectors and regions.
Keywords: H25; H81; Q58; O38; 330; Green Transition Subsidies; Digitalization Support; State Subsidies; Environmental Policy Funding; Sectoral and Regional Allocation; Industrial Policy